(untitled) - Nguyen, Duong Que Hang (Can Tho, 2015)
This study was conducted in order to investigate the undergraduate English majors' perspectives on learner autonomy in English learning. Both quantitative and qualitative data were collected from 270 undergraduate students who responded to a questionnaire, and ten volunteering to respond to an interview.
Keywords: Tiếng Anh,English language; Dạy và học,Study and teaching